The cultural sector in Polish economy in the regional approach - Stanowicka, Agnieszka; Kobylińska, Małgorzata (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: In recent years, the impact of cultural factors on the economic development has been analysed. This research concerns the impact of culture on the labour market, the growth of innovation and creativity, participation in creating added value of GDP, stimulating exports, although the cultural sector also affects the development of tourism, entertainment and improvement in the quality of life of residents. Currently, the cultural sector is treated as a long-term economic investment affecting the development of the country. Aim: The goal of the article is to evaluate the functioning of the cultural sector in Poland. This assessment has been made on a regional basis. Results: To achieve the purpose, data of the GUS (Central Statistical Office in Poland) were analysed. The data concerned expenses allocated to culture and national heritage — they included individual types of cultural institutions and number of cultural sector entities in 2018–2021. The results of the analysis of the cultural sector have been presented in tables and diagrams. Using an agglomeration method, the Polish provinces were grouped according to values of the analysed categories of expenses allocated to culture and national heritage in the provinces in year 2021. It was noticed that the development of the cultural sector in Poland is uneven, concentrated in the country’s capital, which is typical for less developed countries. Therefore, main barriers to the development of the cultural sector in Poland were identified. The most important obstacles were: underfunding, lack of systemic solutions to support the demand for cultural goods, unfavourable legal and financial conditions for creators of culture, lack of support for cooperation between public and private cultural sector, dependence of the development of the cultural sector on politics, as well as lack of social acceptance of the cultural policy. Culture is also negatively affected by the processes of globalization, commercialization and recently the Covid 19 pandemic.